The explosive force of the leg impulse and its relationship to some variables Biokinmatical and accuracy in performing the head scoring skill of jumping in soccer - Bennaceur, abderrahmane; Mouissi, farid (sports creativity, 2025)
The study aimed to identify some of the kinematic variables of the head scoring skill of football players and the relationship between the explosive force of the leg impulse some kinematic variables and the accuracy in the performance of the head scoring skill from jumping in football. The researcher followed the descriptive approach, and the research sample was (05) players of the senior category, as they were deliberately chosen of the Sidi Ahmed ben Ali football team that activates in the first regional association of Oran League. The researcher not only made the imaging process with taking the best attempts using a Sony camera at a frequency of 50 )fps(, but also used the kenovea program to extract the values of the kinematic variables under study; more over, he relied on the spss statistical program to process the data. as a result, a significant correlation relationship was found between the explosive force and some kinematics and precision in performing the head scoring skill from jumping in Football